A novel expression for effective radius in calculating the resonant frequency of circular microstrip patch antennas - Akdagli, Ali (Microwave and optical technology letters, 2007)
This letter presents a novel effective radius expression for determining the resonant frequency of circular microstrip patch antennas. The effective patch radius expression is constructed by using differential evolution algorithm and is valid for both electrically thin and thick circular microstrip antennas (MSAs). It is well suited to be used in the development of fast computer aided design algorithms. Numerical results obtained for the resonant frequencies of circular MSAs are in good agreement with the experimental results reported by several scientists. © 2007 Wiley Periodicals, Inc. Microwave Opt Technol Lett 49: 2395–2398, 2007; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.22767